Organising CSR for gender equality: institutional work in the cocoa value chain - McCarthy, Lauren (2015)
This thesis addresses the burgeoning practice of Corporate Social Responsibility (CSR) programmes and policies that aim to promote gender equality in global value chains. It first presents a conceptual framework for studying gender change within CSR, conceptualising gender as an institution alongside the theory of institutional work. An embedded case study provides rich empirical data from 3 partnered organisations: a UK chocolate company, a UK NGO, and a Ghanaian cocoa supplier as well as 48 cocoa farmers. Drawing on data spanning 20 years, the study interrogates how gender is translated into ‘engendered’ CSR, and how understandings and experiences of gender may be altered by such practices.